O Índice de Participação Cidadã de Medellín (IPCM) e sua contribuição para a sociedade e democracia participativas - Borges, Ananda Beltran (Universidade do Vale do Rio dos Sinos, 2022)
This dissertation focuses on the measurements of citizen participation, elaborated as the Citizen Participation Index, and its contribution to the quality of democracy and public management, based on the analysis of the case of Citizen Participation Index from Medellín, also aiming at the possibility of dissemination of this instrument and the public policies involved. Medellín is currently a reference of social innovation, through the collective achievements and the development of policies and programs involving the population, in addition to the implementation of the Medellín Citizen Participation Index, measured in 2017, 2019 and 2021. For the collection of information, the institutions and organizations responsible were accessed and a documentary analysis of the bibliographic was performed with the material. At the same time another exploratory investigation process was carried out with the social actors and authorities involved in the development and application of the index. From the quantitative and qualitative data used, the strengths, weaknesses, opportunities and threats of the Medellín Citizen Participation Index - IPCM- as an initiative and a public policy project to be implemented in other cities were pointed out. It was concluded with the present study that the elaboration and application of the IPCM resulted in a great theoretical and empirical leap on citizen participation, qualifying its analysis, deepening its dimensions and serving as a basis for the elaboration of public policies. Thus, the elaboration of the IPCM brings theoretical and empirical advances to be explored in current democratic theories. As an initiative that has been recognized as social innovation in the functional phase, its replicability is possible, just as it can be scalable. However, it is a complex process that involves, above all, the political will to opportunize its realization and actors and organizations prepared to take advantage and create the necessary actions and articulations.
Keywords: Participação cidadã; índice de participação cidadã; Teorias democráticas; Citizen participation; Citizen participation index; Democratic theories; ACCNPQ::Ciências Humanas::Sociologia